Strain and displacement measurement based on distributed fibre optic sensing (DFOS) system integrated with FRP composite sandwich panel. (April 2021) - Kulpa, Maciej; Howiacki, Tomasz; Wiater, Agnieszka; Siwowski, Tomasz; Sieńko, Rafał
Highlights: Distributed fibre optic sensors (DFOS) can be integrated with FRP laminates. Installation during production allows the analysis to be done from real "zero state". Integrated DFOS system can accurately measure extremely large strains. Appropriate arrangement of DFOS sensors allows for displacement (shape) analysis. Smart, self-diagnostic components can improve the safety of bridge infrastructure. Abstract: An increase in application of advanced materials and high-tech monitoring systems is being observed in bridge engineering in recent years. The main goal is aimed at optimizing maintenance costs spent during entire lifecycle of a bridge. The paper describes the concept of the smart fibre reinforced polymer (FRP) sandwich deck panel, dedicated for newly-designed and renovated bridges. This panel is equipped with the distributed fibre optic sensing (DFOS) system, integrated with composite laminates. The DFOS system is provided to control strain and displacement measurement, further used in the structural health monitoring of a bridge. The DFOS system is characterized by the following features: accurate, reliable and distributed strain measurements, possibility of assessing shape and displacements, detection of local damages, reliable protection of the sensors, no need for surface installations, high durability, measurements from the real zero state of the structural element. Exemplary results of distributed fibre optic strain and displacement measurements performed under laboratory conditions on laminate specimens as well as the beam cut from the prototype panels are presented and compared to conventional measurements and FEM predictions.